Pemahaman Peraturan Perpajakan, Sosialisasi Pajak, Tarif Pajak dan Kepatuhan Wajib Pajak UMKM - Yastini, Ni Made; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p03, 2022)
This study aims to analyze the effect of understanding tax regulations, socialization of taxation and tax rates on compliance with MSME taxpayers. The study used the method of distributing questionnaires. The research subject is MSME taxpayer compliance in Gianyar Regency. The research was conducted at KKP Pratama Gianyar, with a sample of 99 MSME taxpayers. Analysis of research data using multiple linear analysis. Research shows understanding of tax regulations, tax socialization, and tax rates have a positive influence on compliance with MSME taxpayers in Gianyar Regency. So it can be concluded that MSME taxpayers will comply if they understand tax regulations, there is tax socialization and fair tax rates for MSMEs. Keywords: Tax; MSME; Tax Regulation.